Cysticercosis of masseter - B Dilip Kumar; Bindi Dave; S M Meghana (Wolters Kluwer Medknow Publications, 2011)
Cysticercosis is a parasitic infestation caused by the larval stage of Taenia solium, a cestodic paratise. It is a common disease in developing countries where it is also endemic. The most commonly infested body organs include subcutaneous tissues, brain and skeletal muscles. It is interesting to note that oral lesion of cysticercosis is a rare event. Here we report an isolated lesion of cysticercosis in the masseter muscle.